1996
DOI: 10.1177/08959374960100020501
|View full text |Cite
|
Sign up to set email alerts
|

Transient Accumulation of Proteins At Interrod and Rod Enamel Growth Sites

Abstract: Conceptually, there should be a brief interval in time when newly secreted proteins "pile up" at secretory sites just outside the membrane of ameloblasts. Indeed, previous cytochemical studies have suggested that glycosylated and/or sulfated glycoproteins accumulate at enamel growth sites. Colloidal gold lectin cytochemistry and immunocytochemistry with antibodies to enamel proteins and phosphoserine, combined with cycloheximide and brefeldin A to inhibit protein synthesis and secretion, were applied to charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 72 publications
2
14
0
Order By: Relevance
“…Even though it has been reported that odontoblasts express amelogenin mRNA (Veis et al 2000;Oida et al 2002) and that amelogenin is expressed in relatively small amounts in a temporal-dependent pattern by rodent odontoblasts (Papagerakis et al 2003), the odontoblasts were never labeled in either the control or treated specimens, thus confirming previous studies with the same antibody (Nanci et al 1996;Bosshardt and Nanci 1997;Arana-Chavez and Nanci 2001). At least 14 isoforms are translated by an alternative splicing that takes place during amelogenin processing (Tompkins et al 2005b).…”
Section: The Journal Of Histochemistry and Cytochemistrysupporting
confidence: 65%
See 1 more Smart Citation
“…Even though it has been reported that odontoblasts express amelogenin mRNA (Veis et al 2000;Oida et al 2002) and that amelogenin is expressed in relatively small amounts in a temporal-dependent pattern by rodent odontoblasts (Papagerakis et al 2003), the odontoblasts were never labeled in either the control or treated specimens, thus confirming previous studies with the same antibody (Nanci et al 1996;Bosshardt and Nanci 1997;Arana-Chavez and Nanci 2001). At least 14 isoforms are translated by an alternative splicing that takes place during amelogenin processing (Tompkins et al 2005b).…”
Section: The Journal Of Histochemistry and Cytochemistrysupporting
confidence: 65%
“…Unosmicated sections were directly processed for immunolabeling. Grids were incubated with a chicken egg yolk anti-rat 24-kDa amelogenin antibody (Nanci et al 1996) diluted 1:150 for 5 hr and then incubated with a rabbit anti-chicken IgG secondary antibody (Sigma; St Louis, MO), diluted 1:2000 for l hr. The sites of antibody-antigen binding were revealed with a protein A-gold complex, prepared as described in Bendayan (1995).…”
Section: High-resolution Postembedding Immunocytochemistrymentioning
confidence: 99%
“…The organic phase of developing enamel in optimally fixed teeth appears morphologically homogeneous by electron microscopy. This suggests that constituent amelogenins and various anionic proteins may be uniformly spread, as intact proteins or fragments, throughout the thickness of the enamel layer, albeit in decreasing total bulk amounts forward in time as enamel matures (discussed in Nanci et al 1996). There are several lines of evidence suggesting that this is not the case.…”
mentioning
confidence: 87%
“…There are several lines of evidence suggesting that this is not the case. Both newly secreted matrix proteins present at the forming surface of the enamel layer and partially degraded molecular forms located deeper into it can be concentrated at, or relatively missing from, specific sites within the layer (Smith et al 1989a,b;Kogaya 1994;Nanci et al 1996;Murakami et al 1997;Uchida et al 1991aUchida et al ,b,1997. The most dramatic differences in intraenamel protein concentrations have been observed for nonamelogenins such as ameloblastin and enamelin, for which newly secreted forms are present in high concentration at the enamel surface near ameloblasts (Hu et al 1997a,b;Murakami et al 1997;Uchida et al 1997).…”
mentioning
confidence: 99%
“…Briefly, for the amelogenin class, sections were transferred either on a drop of a chicken egg yolk antibody (Gassmann et al 1990) raised against 24-kD rat amelogenin (AMELy) Nanci et al 1996b), diluted 1:150 for 3 hr, or against mouse recombinant 179 amelogenin isoform (M179y) (Orsini et al in press) diluted 1:100 for 3 hr. They were washed with PBS, refloated on PBS-Oval, and then incubated for 1 hr with a rabbit anti-chicken IgG antibody (diluted 1:2000) (Cappel Research Products; Scarborough, ON, Canada).…”
Section: Immunocytochemistrymentioning
confidence: 99%